EVOLVING MONETARY ECONOMICS IN ISLAMIC PERSPECTIVE - Muhammad Ayub; M. Fahim Khan (Bank Indonesia, 2021)
The challenges facing the Islamic banking and finance industry include, inter alia, resolving the issue of ‘form over substance’, adopting value-based social and ethical finance, and reinforcing public confidence that its business and services conform to the principles of Shari’ah in both letter and spirit. These challenges can be faced only if Islamic finance is based on the money and monetary perspective of Islamic economics. An important aspect for discussion in this context is the issue of money creation. This paper is based on an analysis of the literature on conventional and Islamic economics and Islamic finance. It comprises observational and narrative research mainly because monetary policy from an Islamic perspective has not been implemented in any jurisdiction in the modern world. Its objective is thus to suggest how monetary policy might evolve from the perspective of Islamic law of contracts. It discusses an economic model in which a new theory of monetary economics could become a basis for evolving Islamic finance in its value-based perspective. It also discusses monetary economics and monetary policy from an Islamic perspective in the context of contemporary Muslim economies. The Islamic financial system must be based on the Islamic system of money, monetary economics and exchange principles. Hence, economists and policymakers may first focus on evolving monetary economics and policy from an Islamic perspective, to serve as a basis for structural reforms.